2007
DOI: 10.2459/01.jcm.0000278443.58870.26
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve annuloplasty with a semirigid annuloplasty band in ischemic mitral regurgitation: early results

Abstract: Early and mid-term mitral valve function is satisfactory with trigone-to-trigone semirigid band annuloplasty, with excellent repair durability immediately after the operation and at two years. Moreover, after annuloplasty repair, an improvement in clinical functional status is obtained. A wider use of this semirigid annuloplasty band can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the ICM group, 10 studies 42Y44, 46,47,51,52,54,55,57 (14 inputs) reported a preoperative and postoperative LVESD (Table 7). No difference between the groups was found in study size, fraction of concomitant CABG, mean age, and follow-up.…”
Section: Left Ventricular End-systolic Diametermentioning
confidence: 99%
“…In the ICM group, 10 studies 42Y44, 46,47,51,52,54,55,57 (14 inputs) reported a preoperative and postoperative LVESD (Table 7). No difference between the groups was found in study size, fraction of concomitant CABG, mean age, and follow-up.…”
Section: Left Ventricular End-systolic Diametermentioning
confidence: 99%
“…ICM group: 10 42Y44, 46,47,51,52,54,55,57 studies (14 inputs) reported a preoperative and postoperative LVEDD (Table 7). No difference in study size, fraction of concomitant CABG, mean age and follow-up was found.…”
Section: Left Ventricular End Diastolic Diametermentioning
confidence: 99%
“…Mitral valve repair is generally preferred whenever possible based on valve pathology and patient stability: it avoids longterm anticoagulation, decreases infective endocarditis risk, and provides greater leaflet durability. Among repairs, different techniques are available, but annuloplasty with prosthetic ring is the gold standard [41,42]. On the other hand, valve replacement is usually reserved for situations where the valve cannot be reasonably repaired, or when repair is unlikely to be tolerated clinically.…”
Section: Ischaemic Mitral Regurgitationmentioning
confidence: 99%